Mechanical behaviour and pore morphology of functionally graded alumina preforms and their composites. Issue 8 (July 2023) - Ho, Eric; Scarpa, Fabrizio; Su, Bo
Abstract: Functionally-graded ceramic composites were produced using a hot pour-and-set method via freeze casting of alumina slurries with solid loading between 40% and 20%, with gelatine as a binder. The slurry and additives were tailored for controlling the microstructure and mechanical properties, such as pore morphology, preform density and compressive strength. Varying the gelatine concentration between 2.5% and 9%, transformed the pore morphology from lamelllar to honeycomb and into closed cell. At 3% concentration, increasing the solid loading from 10% to 30% yielded higher compressive strength from 48 MPa to 317 MPa. The resultant compressive behaviour closely matched to Gibson-Ashby closed cell predictive model. Alumina/epoxy composite mechanical performance plateau as the solid loading increased; the 20% solid loading composite produced the best performance. The compressive strengths of the alumina/epoxy and alumina/aluminium composites were on average 300% and 1110% higher than their respective preform counterparts, across a solid loading range of 10–20%.